Externalities in the Urban Economy - Erik T. Verhoef; Peter Nijkamp (Tinbergen Institute, 2003)
This paper is concerned with the economics of urban externalities. We start by reviewing the literature on urban externalities, and observe that although many interesting contributions have been made, there seems to be sufficient scope and need for further research, both theoretically and empirically. We identify what we believe to be important advances to be pursued in future research on urban externalities. These include (1) the explicit consideration of mutual interactions between externalities; (2) a thorough analysis of the relationship between these externalities and urban form; and (3) a clear focus on (realistic) second-best policies. The importance of these issues is illustrated by developing a simple urban general equilibrium model in which we study the interactions between agglomeration externalities and pollution from commuting. Our results show that seemingly impossible findings from a non-spatial perspective, namely a simultaneous stimulation of agglo!meration externalities and a reduction of environmental externalities, is in fact the outcome of first-best policies in our spatial model. Moreover, while the incentives from road pricing and labour subsidies would seem to be perfectly opposite in a non-spatial setting, leaving one of the two instruments redundant, our results show that their welfare effects may, in contrast, turn out to be strongly super-additive when a spatial perspective is taken.
Keywords: D62; R13; R14; 330; Urban equilibrium; environmental and agglomeration externalities; second-best regulation; Stadtökonomik; Externer Effekt; Agglomerationseffekt